Analyzing the Impact of Poverty, Unemployment, and Education on the Human Development Index (HDI) in Sragen Regency - Engelica, Heni; Chasanah, Kamalia Uswatun (Department of Islamic Economics, Faculty of Islamic Economics and Business, Universitas Islam Negeri Sunan Kalijaga, 2025)
This study aims to analyze the effect of poverty rate, unemployment rate, and education level on the Human Development Index (HDI) in Sragen Regency. Using annual time series data from 2015 to 2024 obtained from the Central Bureau of Statistics, the study applies multiple linear regression with the Ordinary Least Squares (OLS) method. The results show that the education variable has a positive influence on HDI and is nearly significant, while poverty and unemployment have negative but insignificant effects. Despite the lack of statistical significance, the direction of the relationship aligns with theoretical expectations. The classical assumption tests indicate that the model is free from multicollinearity, heteroscedasticity, and autocorrelation, and the residuals are normally distributed. These findings suggest that improving education should remain a development priority, while poverty and unemployment need continuous attention to support human development in Sragen.